ANALISIS EFISIENSI PENYALURAN AIR IRIGASI KAWASAN KEMUMU KABUPATEN BENGKULU UTARA (Tinjauan saluran sekunder) - Rahayu, Aditta Setio; Amri, Khairul; Besperi, Besperi (Inersia: Jurnal Teknik Sipil, 2017)
Irrigation efficiency is a major determinant in the system of scheme irrigation . Irrigation efficiency is assumed as part of water would be lost either in the channel or at the rice terraces. Water loss estimate in efficiency include loss of water efficiency tertiary and secondary level, water loss is influenced by the length of the channel, the surface area of the channel, the wet cross section and the position of groundwater. The analysis in this study is to calculate thevalue of the efficiency the secondary and the tertiary canals of irrigation of Kemumu, North Bengkulu. Efficiency is accounted based on the length of the channel, sectional area of wet channel, water velocity, water loss, evaporation and seepage channel. The water loss average of secondary channel is 26,12 mm3/sec. seepage average for secondary channel is 5,06 x 10 mm/day. Evaporation in one year is 0,05 mm/day. The results of this study stated that the efficiency of the secondary channel efficiently deliver water from the primary channel to channel tertiary the average of efficiency  is about 11,92%. The result of this analysis is expected that not efficient channels in Kemumu North Bengkulu can be fixed, so thewater that rice field needed can be fulfilled. The channels can be fixed with some ways, such as making theconcrete irrigation and doing the rutine maintenance.